Committee Opinion No. 667: Hospital-Based Triage of Obstetric Patients. Issue 1 (July 2016) - N/A,
Abstract : ABSTRACT: Emergency departments typically have structured triage guidelines for health care providers encountering the diverse cases that may present to their units. Such guidelines aid in determining which patients must be evaluated promptly and which may wait safely, and aid in determining anticipated use of resources. Although labor and delivery units frequently serve as emergency units for pregnant women, the appropriate structure, location, timing, and timeliness for hospital-based triage evaluations of obstetric patients are not always clear. Hospital-based obstetric units are urged to collaborate with emergency departments and hospital ancillary services, as well as emergency response systems outside of the hospital, to establish guidelines for triage of pregnant women. Recently developed, validated obstetric triage acuity tools may improve quality and efficiency of care and guide resource use, and they could serve as a template for use in individual hospital obstetric units.